THE EFFECTIVENESS OF INQUIRY LEARNING IN READING NARRATIVE TEXT FOR TENTH GRADERS OF SMK NEGERI 1 SOOKO MOJOKERTO (RETAIN, 2016)
THE EFFECTIVENESS OF INQUIRY LEARNING IN READING NARRATIVE TEXT FOR TENTH GRADERS OF SMK NEGERI 1 SOOKO MOJOKERTO Desi Ambar Sari English Education Program, Language and Art Faculty, State University of Surabaya desisari@mhs.unesa.ac.id Drs. Fahri, M.A. English Education Program, Language and Art Faculty, State University of Surabaya Fahri@unesa.ac.id Abstrak Penelitian ini di lakukan berdasarkan penelitian sebelumnya di SMK Negeri 1 Sooko Mojokerto yang mana para siswanya mendapatkan kesulitan untuk memahami teks Narasi. Pada kenyataanya para siswa mendapatkan kesulitan karena suasana belajar yang yang monoton.Penelitian ini di lakukan di SMK Negeri 1 Sooko Mojokerto tepatnya di kelas sepuluh jurusan Administrasi Perkantoran. Tujuan dari penelitian ini adalah untuk membantu siswa untuk dapat memahami teks Narasi berbahasa Inggris dengan menggunakan metode pembelajaran Inquiry Learning. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas. Penelitian ini dilakukan dengan kolaborasi dengan Pengajar di kelas tersebut. Penelitian ini di lakukan selama dua kali putara. Dimana terdapat beberapa tahap di dalamnya yaitu; perencanaan, tindakan, observasi dan refleksi.Penelitian ini menunjukkan bahwa Inquiry Learning dapat membantu siswa memahami teks narasi berbahasa Inggris. Dapat di lihat dari kemampuan para siswa untuk membuat pertanyaan dan jawaban yang sejalan dengan indicator yang buat oleh Brown (2004). Ini menunjukkan bahwa Inquiry Learning dapat membantu menagatasi kesulitan siswa untuk memahami teks Narasi.Bedasarkan hasil penelitian tersebut, dapat di rumuskan dua saran yang pertama untuk Pengajar agar menggunakan metode Inquiry Learning sebagai variasi ketika mengajarkan teks Narasi. Yang kedua, untuk peneliti selanjutnya yang berminat untuk meneliti Inquiry Learning untuk mencoba di bentuk teks yang lainnya. Kata Kunci: Inquiry Learning, Reading, Narrative text Abstract The study was conducted based on the preliminary study in SMK Negeri 1 Sooko Mojokerto which presented that the SMK Negeri 1 Sooko Mojokerto students especially the tenth graders of Office department get difficulty to comprehend the reading text. In reality, they are getting difficulty and feeling bored during the teaching and learning process.The study was conducted in SMK Negeri 1 Sooko Mojokerto especially the Tenth Graders of Office administration department. The aimed of the study is to help the student of the class in comprehending the reading narrative text by implementing Inquiry Learning. The design of the study was classroom action research. The researcher did collaboration with the teacher. This research was conducted in two cycles which is in each cycle was divided into four stages; planning, acting, observing and reflecting. The research findings are presented that Inquiry Learning was able to help the student to comprehend the reading narrative text. It is proved by the ability of the students to create questions and answer related to the text based on Brown indicators. Moreover, it conclude that Inquiry Learning could help the student comprehend the text because the students was getting pleasure during the teaching and learning process and they can understand the text so they could create question and answer based on the text given by the teacher. It means that Inquiry Learning can help the students of SMK Negeri 1 Sooko Mojokerto comprehending the reading narrative text.Based on the research findings, there are two suggestions. First, the English teacher is recommended to implement Inquiry Learning to vary the teaching method in teaching reading narrative text. The second, for the next researchers who are interested to conduct a research by Implementing Inquiry Learning is recommended to conduct the research in different kinds of reading text. Keywords: Inquiry Learning, Reading, Narrative text